MODERN VIEWS ON ETIOLOGY OF CHRONIC PANCREATITIS AND CORRECTION OF FUNCTIONAL INSUFFICIENCY OF THE PANCREAS - E. А. Kornienko; A. A. Yagupova ("Paediatrician" Publishers LLC, 2012)
Chronic pancreatitis is a multietiological disorder characterized by progressive structural changes of the pancreas and development of its eccrine and endocrine insufficiency. The potential causes of chronic pancreatitis in children include obstruction of the pancreas ducts due to cholelithiasis, chronic cholecystitis with biliary sludge, excretory ducts anomalies; obesity and hyperlipidemia; abdominal traumas and infectious pancreatic diseases. Recently new possible variants of chronic pancreatitis - autoimmune and hereditary - have been diagnosed due to the widening of diagnostic potentials. Fifty children and adolescents with chronic pancreatitis were diagnosed. It was shown, that obstructive chronic pancreatitis was found in 50%, obesity-associated. According to the literature, more than 70% of children with idiopathic chronic pancreatitis have genetic mutations in genes SFTR, PRSS1 and SPINK1, both single and associated. These lead to imbalance of the trypsinogen activation and inactivation in the pancreas tissue. Severe mutations can be an independent cause of chronic pancreatitis, mild ones manifest after the impact of some external factors. Regardless of the cause of the disease, the mandatory component of the treatment is enzyme replacement therapy with the preference to microspherical forms.